Curcumin-loaded redox-responsive mesoporous silica nanoparticles for targeted breast cancer therapy. (5th November 2018) - Li, Nana; Wang, Zhi; Zhang, Yongtai; Zhang, Kai; Xie, Jianxu; Liu, Ying; Li, Wansi; Feng, Nianping
Abstract: Hypothesis: The antitumor applications of curcumin (CUR) are limited because of its low water solubility, poor stability, and low bioavailability. We developed novel nanocarrier systems for tumour targeting and controlled CUR release and evaluated their therapeutic efficacy. Experiments: The surface of mesoporous silica nanoparticles (MSN) was modified with hyaluronan (HA) or polyethyleneimine-folic acid (PEI-FA) via disulfide bonds. The capacity of the resultant nanocarriers (MSN-HA and MSN-PEI-FA, respectively) for CUR delivery was evaluated in a breast cancer cell line and a mouse xenograft model. Findings: MSN/CUR-PEI-FA and MSN/CUR-HA were cytotoxic to MDA-MB-231 breast cancer cells. Both formulations showed an enhanced cellular uptake compared with that of a non-targeted nanocarrier, with a greater cellular uptake of FA-modified nanoparticles than that of HA-modified nanoparticles. Accordingly, MSN-PEI-FA showed more precise targeting and higher accumulation in tumours than did MSN-HA, as visualized by live imaging. Both types of nanoparticles had good biocompatibility and low toxicity, and MSN/CUR-PEI-FA inhibited the tumour growth to a greater degree than did free CUR. Thus, MSN/CUR-PEI-FA are a promising drug delivery system for the treatment of breast cancer.